Effect of Addition of Turmeric (Curcuma longa) and Ginger (Zingiber officinale) on Feed Intake and Growth Performance in Broilers - Joshi, Monika; Ram, Uma; Sharma, Shiv Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The aim of this study was to evaluate the effect of the addition of Turmeric (Curcuma longa) and Ginger (Zingiber officinale) alone andin combination on feed intake and growth performance in broilers. A total of 180 one-day-old broiler chicks (VENCOBB) were broodedfor 2 weeks, then randomly allocated into four treatments with three replicates of 15 birds each. Group T1 Birds were fed on basal diet,T2 and T3 supplemented with turmeric powder and ginger powder @1.5 %, respectively, and T4 group birds were fed 0.75 % turmericpowder and 0.75% ginger powder in combination. All the treatment groups were further divided into three replicates, viz., R1, R2, and R3(n=15 chick each). Statistical analysis of data revealed that there were no significant differences in the overall average daily feed intakeand weekly feed intake but there was a highly significant difference (p
Keywords: Broilers; Ginger; , Growth performance; Herbal feed additives; Turmeric